2020
DOI: 10.1111/jsr.12994
|View full text |Cite
|
Sign up to set email alerts
|

Exploring scoring methods for research studies: Accuracy and variability of visual and automated sleep scoring

Abstract: Sleep studies face new challenges in terms of data, objectives and metrics. This requires reappraising the adequacy of existing analysis methods, including scoring methods. Visual and automatic sleep scoring of healthy individuals were compared in terms of reliability (i.e., accuracy and stability) to find a scoring method capable of giving access to the actual data variability without adding exogenous variability. A first dataset (DS1, four recordings) scored by six experts plus an autoscoring algorithm was u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 43 publications
0
30
0
Order By: Relevance
“…Sleep staging was performed with an automatic scoring algorithm (ASEEGA, version 4.4.23, PHYSIP, Paris, France) which has been successfully used in previous studies (Reichert et al, 2017;Gaggioni et al, 2019) and has been shown to reach good agreement with manual sleep scoring (Berthomier et al, 2020). Three data sets were excluded from analyses of allnight variables concerning the entire sleep episode due to technical issues (placebo condition: n = 2; caffeine condition: n = 1) and one volunteer was excluded from all analyses of REM sleep parameters (placebo condition) based on potential missed REM sleep episode by the algorithm and disagreement with visual scorers.…”
Section: Eeg Recordingsmentioning
confidence: 99%
“…Sleep staging was performed with an automatic scoring algorithm (ASEEGA, version 4.4.23, PHYSIP, Paris, France) which has been successfully used in previous studies (Reichert et al, 2017;Gaggioni et al, 2019) and has been shown to reach good agreement with manual sleep scoring (Berthomier et al, 2020). Three data sets were excluded from analyses of allnight variables concerning the entire sleep episode due to technical issues (placebo condition: n = 2; caffeine condition: n = 1) and one volunteer was excluded from all analyses of REM sleep parameters (placebo condition) based on potential missed REM sleep episode by the algorithm and disagreement with visual scorers.…”
Section: Eeg Recordingsmentioning
confidence: 99%
“…Scoring of sleep stages was performed automatically in 30-s epochs using a validated algorithm (ASEEGA, PHYSIP, Paris, France) 31 and according to 2017 American Academy of Sleep Medicine criteria, version 2.4. An automatic artefact detection algorithm with adapting thresholds 32 was further applied on scored data.…”
Section: Eeg Acquisitions and Analysesmentioning
confidence: 99%
“…EEG data were re-referenced off-line to average mastoids. Scoring of sleep stages was performed automatically in 30-s epochs using a validated algorithm (ASEEGA, PHYSIP, Paris, France) 31 and according to 2017 American Academy of Sleep Medicine criteria, version 2.4. An automatic artefact detection algorithm with adapting thresholds 32 was further applied on scored data.…”
Section: Methodsmentioning
confidence: 99%